2020
DOI: 10.1371/journal.pone.0236080
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of exclusive breastfeeding practice in Bangladesh: Evidence from nationally representative survey data

Abstract: Background Exclusive breastfeeding (EBF) means that an infant should be breastfed only for the first six months of life to achieve optimal child development and to prevent infant morbidity and mortality. The aim of this analysis was to determine the individual-, household-, and communitylevel factors associated with EBF practice in Bangladesh. Methods A total of 1,440 women-child pairs data were analysed extracted from 2011 and 2014 Bangladesh Demographic and Health Survey. Multilevel logistic regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 35 publications
9
26
1
Order By: Relevance
“…Mothers from socioeconomically privileged class would have higher coverage of EBF in contrast to their counterparts in lower socioeconomic class. This is in line with a previous study which found a connection between household wealth, maternal education and infant breastfeeding, as only about one-tenth of mothers who practiced EBF came from poor households and without formal education, in contrast to their well-off and educated counterparts with over one-quarter coverage of EBF [5,31,[58][59][60]. Therefore, our evidence of a positive association between maternal education and improvement in EBF is well founded.…”
Section: Discussionsupporting
confidence: 93%
“…Mothers from socioeconomically privileged class would have higher coverage of EBF in contrast to their counterparts in lower socioeconomic class. This is in line with a previous study which found a connection between household wealth, maternal education and infant breastfeeding, as only about one-tenth of mothers who practiced EBF came from poor households and without formal education, in contrast to their well-off and educated counterparts with over one-quarter coverage of EBF [5,31,[58][59][60]. Therefore, our evidence of a positive association between maternal education and improvement in EBF is well founded.…”
Section: Discussionsupporting
confidence: 93%
“…Community-level factors that were considered in the analysis were the place of residence (urban and rural), region of residence (Barishal, Chattogram, Dhaka, Khulna, Rajshahi, Rangpur, and Sylhet), community-level literacy (≤25%, 26–50, and > 50%), community-level poverty (high, moderate, low, and middle-to-richest), and community-level uptake of at least four ANC visits (> 50% and ≤ 50%). These variables were categorized following previous studies in Bangladesh [ 40 , 41 ]. Women’s responses to the questions related to literacy, poverty, and ANC use across clusters were used to generate community-level responses on literacy, poverty, and ANC use, which were not directly available in the dataset used.…”
Section: Methodsmentioning
confidence: 99%
“…Breastfeeding prevents the introduction of potentially contaminated prelacteal foods, provides newborns with colostrum (rich in a variety of nutrients and immunoglobulins) and protects against diarrheal diseases and respiratory tract infection [ 7 , 8 , 9 , 10 , 11 , 12 ]—two leading causes of preventable under-five-years deaths in Bangladesh [ 13 ]. Numerous research from Bangladesh has identified the determinants of breastfeeding (BF) practices among mothers of all age groups [ 14 , 15 , 16 , 17 , 18 ]. However, specific studies that focus on breastfeeding practices of adolescent mothers are limited.…”
Section: Introductionmentioning
confidence: 99%